THE NURSE'S ROLE IN THE PREGNANCY-PUERPERAL CYCLE: POSTPARTUM WOMEN'S PERCEPTION IN THE LIGHT OF PEPLAU'S THEORY - Lima, Kelly Suianne de Oliveira; Bezerra, Tamires Barbosa; Pinto, Antonio Germane Alves; Quirino, Glauberto da Silva; Sampaio, Luis Rafael Leite; Cruz, Rachel de Sá Barreto Luna Callou (Cogitare Enfermagem, 2024)
Objective: to analyze postpartum women's perceptions of the role of nurses in the pregnancy-puerperal cycle in light of Peplau's theory. Method: a descriptive study with a qualitative approach, using Peplau's Theory as its theoretical-methodological framework. Data was collected at a Normal Birth Center in Ceará - Brazil, from March to May 2021. A semi-structured interview was conducted with 30 postpartum women. The analysis took place according to the phases of the theory: orientation, identification, exploration, and resolution. Results: the information provided by nurses was not satisfactorily understood and women's autonomy during labor was restricted. Resources such as birth plans and pregnancy groups were not effectively explored. The postpartum women were predominantly satisfied with the resolution of their care. Conclusion: The importance of applying Peplau's theory to nursing care in the puerperal pregnancy cycle was highlighted to promote women's autonomy in the therapeutic process.